Phytochemical Compound Identification of Mangrove Leaves Sonneratia alba and in Silico Analysis as Antidiabetic - Yunita Eka Puspitasari; Hardoko Hardoko; Titik Dwi Sulistiyati (Faculty of Fisheries and Marine, Universitas Riau, 2022)
Mangrove plant, Sonneratia alba, can be found abundantly in Indonesia. Some previous studies reported phytochemical screening and bioactivity test of Sonneratia sp. as anti-diabetic (in vitro and in vivo analysis). However, phytochemical identification of S. alba leaves and inhibitory activity of α-glucosidase as anti-diabetic have not been reported. The purpose of this study are to identify phytochemical compounds of methanolic extracts S. alba leaves, and to predict inhibitory mechanisms of S. alba leaves against α-glucosidase through in silico analysis. In this study, the research method consists of two steps namely identification phytochemical compounds of methanolic extracts S. alba leaves, and prediction inhibitory activities of phytochemical compounds of methanolic extracts S. alba leaves against α-glucosidase by molecular docking (in silico) analysis. Methanolic extracts S. alba leaves contained orientin, vitexin, luteolin, oleanolic acid and reserpine. Reserpine was identified for the first time in S. alba leaves. Based on in silico analysis, binding energy of orientin, vitexin, luteolin, oleanolic acid, reserpine and acarbose (positive control) against α-glucosidase were -9,7; -9,7; -9,2; -8,6; -10,0 dan -8,3 kcal/mol. This result indicated that compounds inhibited α-glucosidase activities and can be considered as antidiabetic agent.